Analisis Manajemen Permodalan Pada Baitul Maal Wa Tamwil di Masa Pandemi - Kharis Fadllullah; Maristiya Cahya Lupita (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2022)
Baitul maal wa tamwil is a well-known sharia microfinance organization in the neighborhood. However, because of the poor segmentation of micro-businesses, Covid-19 had a big influence. The purpose of this research is to learn more about the state of capital and capital management in Baitul Maal Wa Tamwil (BMT) Muamalat Mulia. Because BMT Muamalat Mulia caters to the lower-middle market, the area was chosen. This study employs descriptive qualitative research with a case study technique. Interviews and observations are used to gather information. As a result of the existence of inferior funding members, BMT is severely harmed. Nonetheless, BMT Muamalat Mulia is able to endure because to strong capital management, which includes dividing productive capital, non-productive capital, and employing cash to mitigate risks.